2013
DOI: 10.1021/mz400568j
|View full text |Cite
|
Sign up to set email alerts
|

Stereocomplex Formation of Densely Grafted Brush Polymers

Abstract: In this report, we explore the capability of macromolecules to interdigitate into densely grafted molecular brush copolymers. We demonstrate that by using the tendency for stereocomplexation between poly(l-lactide) and poly(d-lactide) as a driving force complementary linear polymers and brush copolymers can form a stereocomplex. However, stereocomplex formation between complementary brush copolymers is restricted and only partially observed when the side chains are of a critical molecular weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 37 publications
0
45
1
Order By: Relevance
“…Previously, Grubbs et al . observed that the stereocomplex formation between the brush PLLA and PDLA is restricted . But their densely grafted brush polymers are different from our grafted systems.…”
Section: Resultscontrasting
confidence: 59%
“…Previously, Grubbs et al . observed that the stereocomplex formation between the brush PLLA and PDLA is restricted . But their densely grafted brush polymers are different from our grafted systems.…”
Section: Resultscontrasting
confidence: 59%
“…The major principle of the stereocomplexation process includes two aspects, i.e., the specific molecular interaction as the driving force and the precise pairing of stereoisomers to keep it growing. The former was responsible for the preferential formation of sc ‐PLA at lower concentrations from solutions or at higher temperatures from the melt, while the latter rationalized the unique triangular single crystals and curvatures of dendritic and edge‐on crystals of sc ‐PLA as a result of unbalanced growths of stereoisomers with different molecular characteristics or amounts.…”
Section: Introductionmentioning
confidence: 99%
“…It happens when the interaction between the polymer chains of different configurations overcome the interaction between polymers with the same configuration . Generally an elevation of the melting temperature is found as a result of successful stereocomplex formation in DSC analysis . In the present work, the interactions between the side‐chains of the homopolymer as well as the copolymer are not strong enough to make them crystallizable as revealed by the absence of any melting temperature peak in the DSC thermogram.…”
Section: Resultsmentioning
confidence: 99%
“…The stereoisomers poly( l ‐lactide) and poly( d ‐lactide) can interact with each other to form such stereocomplexes . Recently, Grubbs and co‐workers reported that the interaction between poly( l ‐lactide) and poly( d ‐lactide) can act as a strong driving force to allowmacromolecules to form stereocomplexes . Also, Longo et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation